Rapid Successful Reperfusion of Basilar Artery Occlusion Strokes With Pretreatment Diffusion‐Weighted Imaging Posterior‐Circulation ASPECTS <8 Is Associated With Good Outcome - Morgan Guillaume; Bertrand Lapergue; Benjamin Gory; Julien Labreuche; Arturo Consoli; Gioia Mione; Lisa Humbertjean; Jean‐Christophe Lacour; Mikaël Mazighi; Michel Piotin; Raphaël Blanc; Sébastien Richard; et al. (2019)
Background The association between time to reperfusion and clinical outcome is well known in anterior circulation strokes, whereas the impact of main time metrics remains unknown in posterior circulation strokes. We investigated the clinical effect of different time intervals from symptom onset to reperfusion on the 90-day clinical outcome in acute ischemic stroke patients with basilar artery occlusion, and especially in the subset population presenting a low stroke volume on baseline diffusion-weighted imaging. Methods and Results We studied patients included in the prospective, multicenter, observational ETIS (Endovascular Treatment in Ischemic Stroke) registry who had had basal artery occlusion and had achieved successful reperfusion (modified Thrombolysis In Cerebral Infarction 2b-3). Three time intervals (onset to reperfusion, onset to imaging, and imaging to reperfusion) were considered in all patients and separately in patients with pc- ASPECTS (posterior-circulation Alberta Stroke Program Early Computed Tomography Score) <8 and ≥8 on baseline diffusion-weighted imaging. The primary end point was good outcome defined as 90-day modified Rankin Scale scores of 0 to 2. Among the 95 included patients, 38 (40%) achieved a good outcome. In all patients, no significant association was found between the different time intervals and outcome. In patients evaluated with diffusion-weighted imaging (n=61) at baseline, a significant negative association was found between imaging-to-reperfusion time for patients with pc- ASPECTS <8 (adjusted odds ratio=0.4 per 30-minute increase; 95% CI 0.18-0.85; P=0.02) compared with those with pc- ASPECTS ≥8. Conclusions In patients with basilar artery occlusion and pc- ASPECTS <8 at baseline diffusion-weighted imaging, clinical outcome is highly dependent on the time from imaging to reperfusion, which suggests that rapid endovascular reperfusion should be performed after imaging in these patients.